RESEARCH ON THE ENERGY ABSORPTION CHARACTERISTICS OF EXPANSION TUBE ENERGY ABSORBING ELEMENTS FOR RAIL VEHICLES - HE ShiZhong; HUANG Ke (Jixie qiangdu)
In this paper, the expansion tube type energy absorbing element was taken as the research object, and 9 samples were tested by automatic electro-hydraulic servo press and large drop hammer impact tester. Based on the experimental data and numerical simulation results, the effects of wall thickness, cone outer diameter and impact velocity on the energy absorption characteristics of energy absorbing components were studied. The test results show that the expansion tube type energy absorbing element is not sensitive to the impact speed. The ratio of the smooth crash force of the energy absorbing element under the drop hammer impact to the smooth crash force of the quasi-static compression is about 0.96～0.98; when the outer diameter of the cone is constant, the force of the energy absorbing element is substantially linear with the wall thickness of the expansion tube; when the wall thickness of the expansion tube is constant, the force of the energy absorbing element is approximately linear with the outer diameter of the cone, and with the outer diameter of the the cone increases, the amount of increase in the force tends to decrease. This paper provides a basis for the design of the expansion tube type energy absorbing element.